SOME CONSIDERATIONS ON THE ECOLOGICAL STATUS OF LAND RESOURCES - Muminov Daniyor Gulomovich; Abdimanapov Bakhadurkhan Sharipovich (Galaxy International Interdisciplinary Research Journal, 2022)
In this work, the issues of research of land resources are covered. Information about the need to take into account the natural geographic, economic geographic, and social geographic factors of the study of land resources is given. Emphasis is placed on aspects of efficient and environmentally safe use of resources.